Transcriptome analysis of resistance mechanism to potato wart disease - Li Peihua (De Gruyter, 2021)
To understand the molecular mechanism of the resistance to potato wart disease, we used the potato cultivar Qingshu 9 as the experimental material and prepared potato samples with different levels of disease through inoculation. The RNAs of the samples were extracted, and transcriptome analysis was performed on the samples not infected by the disease (control group) and also on the samples with different levels of disease, with the aid of high-throughput sequencing. Next, the differentially expressed genes (DEGs) associated with the resistance to potato wart disease were identified based on the analysis results. Using bioinformatic tools, the DEGs were functionally annotated, classified, and enriched in related metabolic pathways. The main results are as follows: Compared with the control group, 4 DEGs were identified in the samples with light disease, 52 were found in the samples with medium disease, and 214 were discovered in the samples with heavy disease. Potato mainly resists the wart disease by suppressing its gene expression, and the degree of suppression depends on the level of the disease; the disease resistance might be dominated by cellular nucleic acid-binding protein, AP2-like transcription factor, and E3 ubiquitin-protein ligase. This research provides new insights into the molecular mechanism of potato resistance against wart disease.